Correlation Between BI-RADS Categories and Yokohama Reporting System of Breast Cytology at a Tertiary Care Teaching Hospital - Presswala, Heli Bharatbhai; Dhotre, Sanjay Vinayak; Faldu, Bhavesh; Barot, Hitendra Pravinkumar; Marvaniya, Arzoo Mansukhbhai; Pateliya, Bharat (Annals of Pathology and Laboratory Medicine, 2025)
Background: The highest level of preoperative diagnostic accuracy of breast lesions can be achieved using the triple approach of clinical examination, breast imaging reporting and data system (BI-RADS) grading by mammography and fine needle aspiration cytology (FNAC). Correlation between BI-RADS categories & cytological findings are useful approach to establish an important and accurate preoperative diagnosis as well as for planning therapeutic protocol in carcinoma of breast considering histopathology as gold standard. Methods: A retrospective study of 100 female patients with palpable breast lump was conducted at B.J. Medical College, Ahmedabad. Patients underwent breast imaging and were categorized according to BI-RADS. FNAC was performed and smears were stained using standard cytological stains. The cytological diagnoses were reported according to the IAC Yokohama system. The correlation between BI-RADS categories and FNAC findings was analyzed. Results: Out of 100 cases, 59 benign, 25 malignant, 13 atypical and suspicious for malignancy and 3 cases were unsatisfactory on FNAC. The most common benign lesion was fibroadenoma (34%), while infiltrating ductal carcinoma (24%) was the predominant malignant lesion. A maximum number of cases were reported in the 31-40 years age group. Concordance between BI-RADS and FNAC was observed in 85% of cases. Conclusion: There is a high correlation between BI-RADS and cytological diagnosis in the assessment of breast lesions. We recommend that both BI-RADS and FNAC are vital investigation in the initial evaluation of patients with breast disease.